2022
DOI: 10.1001/jamanetworkopen.2021.44934
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Mental Health Disorders Among Immigrant, Refugee, and Nonimmigrant Children and Youth in British Columbia, Canada

Abstract: IMPORTANCEThere remains limited understanding of population-level patterns of mental disorder prevalence for first-and second-generation immigrant and refugee children and youth and how such patterns may vary across mental disorders. OBJECTIVE To examine the diagnostic prevalence of conduct, attention-deficit/hyperactivity disorder (ADHD), and mood/anxiety disorders in immigrant, refugee, and nonimmigrant children and youth in British Columbia, Canada. DESIGN, SETTING, AND PARTICIPANTS This retrospective, popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…A total of ten papers are included in the review [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], all of which were published from 2012 to 2022 (see Table 1 ). Ten papers included prevalence estimates of ADHD in Canada [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Out of these papers, one also examined the incidence of ADHD in Canada [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of ten papers are included in the review [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], all of which were published from 2012 to 2022 (see Table 1 ). Ten papers included prevalence estimates of ADHD in Canada [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Out of these papers, one also examined the incidence of ADHD in Canada [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…This group of studies based estimates on data collected from 1999 [ 11 , 20 ] to 2015/6 [ 12 , 17 , 20 ]. The range for data collection was similar for papers that focused on ADHD prevalence in children and/or adolescents (1999–2015/6) [ 11 , 15 , 17 , 18 , 20 ] and those that examined prevalence in adults (1999–2018) [ 13 , 14 , 15 , 16 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Ireland, a qualitative study showed that adolescents and children experienced increased rates of social isolation, maladaptive behavior, anxiety, and depression during the pandemic [32]. Moreover, the pandemic resulted in a significant psychosocial impact on Chinese adolescents and children in terms of emotional distress, with a prevalence of 24.9% for anxiety, 19.7% for depression, and 15.2% for stress [33]. Another systematic review of Chinese studies showed that the prevalence of COVID-19 related posttraumatic stress, sleep disorders, anxiety, and depression were 48%, 44%, 26%, and 29%, respectively [34].…”
Section: Introductionmentioning
confidence: 99%
“…Another study that was published in 2010 reported that 1 in 5 US children experience a serious or debilitating mental health problem in their lifetime [17]. Similar studies from Canada [18, 19], Europe [20, 21], and Australia [22, 23] suggest comparative high burden of child and adolescent mental health (CAMH) problems. Moreover, countries with limited resources, mostly those in the global south, often lack high-quality evidence on mental health epidemiology.…”
Section: Introductionmentioning
confidence: 99%